How Does Water Stress and Nitrogen Fertilizer Affect the Growth and Yield of Upland Rice (Oryza Sativa L.) - Alibu, Simon; Mamadou, Fofana (Journal of Food and Nutrition Research, 2021)
Water stress and inadequate nitrogen (N) fertilizer are important factors that simultaneously limit the growth and yield of upland rice. In this study, we examined the interactive effects of N fertilizer application and water stress timing on the growth and productivity of upland rice. The experiment was set up as a randomized complete block design (RCBD) with 2 replications. Toyohatamochi rice was fertilized with three levels of N (30, 60, and 90 kg/ha) and subjected to water stress at different growth stages (early vegetative, active tillering, maximum tillering stages, and then at 10 and 20 days after heading). We did not find any statistically significant interactive effects of water stress timing and N on growth, yield, and dry matter productivity, although N appeared to increases the sensitivity of upland rice to water stress. Water stress at maximum tillering and 10 days after heading (DAH) both reduced grain yield by 50% and dry matter productivity by 49% and 38% respectively. In contrast, early vegetative stress reduced grain yield by a modest 20% despite decreasing dry matter productivity by 40%. Nevertheless, the grain yield of rice stressed at the early vegetative stage increased with N, suggesting a possibility of salvaging grain yield in rice that has suffered water stress at the early vegetative stage by enhancing N fertilization. However, after maximum tillering but before 20 DAH water stress caused irrecoverable grain yield loss, even with more N.
Keywords: aerobic rice; drought sensitivity; nitrogen fertilizer